Indirect Regulation of PTH by Estrogens May Require FGF23 - Carrillo-López, Natalia (American Society of Nephrology, 2009)
The mechanisms by which estrogens modulate PTH are controversial, including whether or not estrogen receptors (ERs) are present in the parathyroid glands. To explore these mechanisms, we combined a rat model of CKD with ovariectomy and exogenous administration of estrogens. We found that estrogen treatment significantly decreased PTH mRNA and serum levels. We did not observe ERα or ERβ mRNA or protein in the parathyroids, suggesting an indirect action of estrogens on PTH regulation. Estrogen treatment significantly decreased serum 1,25(OH)(2) vitamin D(3) and phosphorus levels. In addition, estrogens significantly increased fibroblast growth factor 23 (FGF23) mRNA and serum levels. In vitro, estrogens led to transcriptional and translational upregulation of FGF23 in osteoblast-like cells in a time- and concentration-dependent manner. These results suggest that estrogens regulate PTH indirectly, possibly through FGF23.